The occurrence of anti-Neospora caninum in bovine female animals and bovine fetuses in Nossa Senhora do Livramento County, Mato Grosso - Robson Souza Rodrigues (Semina: Ciências Agrárias, 2016)
Neosporosis is a parasitic disease caused by the obligate intracellular protozoan Neospora caninum, which is responsible for miscarriage cases in cattle countrywide. The vertical or transplacental route with prevalent miscarriages between the 3rd and 6rd months of pregnancyis the main transmission form in cattle. The aim of the present study is to investigate the presence of anti-N.caninum antibodies in (Bos indicus) Nellore female animals and fetuses in Nossa Senhora do Livramento County - MT. Blood samples from 489 female bovines and from 128 bovine fetuses over three months of pregnancy were colleted. The research about the anti N. caninum antibodies in bovine females and fetuses was conducted through the Immunofluorescence technique (IFA). We found 2.45% (12) seropositive and 3.91% (5) seropositive to N. caninum in the present study.